Soil conditions and cereal root system architecture: review and considerations for linking Darwin and Weaver - Rich, Sarah M; Watt, Michelle (Journal of experimental botany, 2013)
Charles Darwin founded root system architecture research in 1880 when he described a root bending with gravity. Curving, elongating, and branching are the three cellular processes in roots that underlie root architecture. Together they determine the distribution of roots through soil and time, and hence the plants’ access to water and nutrients, and anchorage. Most knowledge of these cellular processes comes from seedlings of the model dicotyledon, Arabidopsis, grown in soil-less conditions with single treatments. Root systems in the field, however, face multiple stimuli that interact with the plant genetics to result in the root system architecture. Here we review how soil conditions influence root system architecture; focusing on cereals. Cereals provide half of human calories, and their root systems differ from those of dicotyledons. We find that few controlled-environment studies combine more than one soil stimulus and, those that do, highlight the complexity of responses. Most studies are conducted on seedling roots; those on adult roots generally show low correlations to seedling studies. Few field studies report root and soil conditions. Until technologies are available to track root architecture in the field, soil analyses combined with knowledge of the effects of factors on elongation and gravitropism could be ranked to better predict the interaction between genetics and environment (G×E) for a given crop. Understanding how soil conditions regulate root architecture can be effectively used to design soil management and plant genetics that best exploit synergies from G×E of roots.